Pengujian Aktivitas Antihiperglikemia Infusa Batang Muda Rotan (Calamus Caesius Blume) Pada Tikus Putih Jantan (Rattus Norvegicus) Galur Wistar Yang Diinduksi Aloksan - Suharyanisa Suharyanisa; Jon Kenedy Marpaung; Dumartina Hutauruk; Juli Susanti (Jurnal Siti Rufaidah, 2023)
Medicinal plants have been known and used worldwide for thousands of years. One type of medicinal plant that is often used is gaharu. The efficacy of gaharu leaves provides properties as a fever reducer, increases appetite, launches menstruation, and relieves pain. This study aims to determine whether there is an analgesic effect from the methanol extract of gaharu leaves in male Wistar rats using the heat stimulation method. This study was an experimental study using twenty-five male Wistar rats divided into five groups. Group I (negative control), rats were treated with 1% CMC-Na. Group II (positive control), rats treated with mefenamic acid 45 mg/kg BW. Group III, IV, and V rats were treated with gaharu leaf methanol extract suspension (100; 200, and 400) mg/kg BW. Pain stimulation was carried out by dipping the rat tail into a 40°C water bath. Data on response time to pain, stimuli were analyzed using the One-Way Analysis of Variance (ANNOVA) method with a 95% confidence level followed by a post-hoc Tukey test to determine which group had the same or significantly different effect. The results showed that the normal response time data for mice to painful stimuli ranged from 2.79 to 3.57 seconds. 1% CMC-Na treatment in mice was unable to increase the response time to a significant pain stimulus (p>0.05). Mefenamic acid treatment 45 mg/Kg BW significantly increased the response time to painful stimuli (p<0.05) with the longest average response time to painful stimuli, namely 8.87 seconds. Based on the method used in this research, methanol extract of agarwood leaves 400 mg/kgBW has almost the same analgesic effect as mefenamic acid 45 mg/KgBW.